Preparation and characterization of a nanohydroxyapatite and sodium fluoride loaded chitosan-based in situ forming gel for enamel biomineralization - Azade Rafiee; Negin Mozafari; Neda Fekri; Mahtab Memarpour; Amir Azadi (Heliyon, 2024)
The development of remineralizing smart biomaterials is a contemporary approach to caries prevention. The present study aimed at formulation preparation and characterization of a thermoresponsive oral gel based on poloxamer and chitosan loaded with sodium fluoride (NaF) and nanohydroxyapatite (nHA) to treat demineralization. The chemical structure and morphology of the formulation were characterized using FTIR and FESEM-EDS tests. Hydrogel texture, rheology, and stability were also examined. The hydrogel was in a sol state at room temperature and became gel after being placed at 37 °C with no significance different in gelation time with the formulation without nHA and NaF as observed by t-test. The FTIR spectrum of nHA/NaF/chitosan-based hydrogel indicated the formation of physical crosslinking without any chemical interactions between the hydrogel components. The FESEM-EDS results demonstrated the uniform distribution of each element within the hydrogel matrix, confirming the successful incorporation of nHA and NaF in the prepared gel. The hardness, hydrogel’s adhesiveness, and cohesiveness were 0.9 mJ, 1.7 mJ, and 0.37, respectively, indicating gel stability and the acceptable retention time of hydrogels. The formulation exhibited a non-Newtonian shear-thinning pseudoplastic and thixotropic behavior with absolute physical stability. Within the limitation of in vitro studies, nHA/NaF/chitosan-based in situ forming gel demonstrated favorable properties, which could be trasnsorm into a gel state in oral cavity due to poloxamer and chitosan and can prevent dental caries due to nHA and NaF. We propose this formulation as a promising dental material in tooth surface remineralization.